PENGUATAN PROFESIONALITAS KJA DI KOTA MALANG MELALUI PELATIHAN KETERAMPILAN KOMUNIKASI DAN PEMAHAMAN ETIKA - Perdana, Sukma; Umamy, Etty; Efendiy, Khoirul; Kristiawan, Indria; Siwi Suwigyo, Hanum Lintang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
This community service program was designed to enhance the professionalism of Accounting Service Offices (KJA) in Malang through training in communication skills and ethical understanding. The program aims to make a significant contribution to improving service quality, maintaining integrity, and supporting the economic development of the community. The community partners comprised professionals from KJA, with the training conducted over three months, involving interdisciplinary lecturers for a holistic approach. The training methods included delivering fundamental materials through seminars, demonstrations and simulations, as well as evaluations and mentoring. Data collection employed a quantitative approach using questionnaires and a qualitative approach through in-depth interviews. Quantitative results revealed that 80% of participants experienced significant improvement in communication skills, while 70% reported enhanced ethical understanding, positively impacting workplace relationships and the professional image of the office. Qualitative findings supported these results, highlighting that the training enhanced participants' ability to make ethical decisions and build harmonious workplace relationships. This program demonstrates that training in communication skills and ethics is a strategic investment to enhance organizational professionalism and integrity. These findings are relevant to strengthening professional services in the service sector and fostering a productive work culture, providing long-term benefits for individuals and organizations.